Odpowiedź :
Odpowiedź:
b-2c/a= 3 + 2√2 - 2(4 - √2) : 1/2 = 3 + 2√2 - 2(4 - √2) * 2 =
= 3 + 2√2 - 4(4 - √2)= 3 + 2√2 - 16 + 4√2 = 6√2 - 13
[tex]3 + 2 \sqrt{2} - \frac{2(4 - \sqrt{2} )}{ \frac{1}{2} } = \\ = 3 + 2 \sqrt{2} - \frac{8 - 2 \sqrt{2} }{ \frac{1}{2} } = \\ = 3 + 2 \sqrt{2} -(( 8 - 2 \sqrt{2} \div) \frac{1}{2} ) = \\ = 3 + 2 \sqrt{2} - ((8 - 2 \sqrt{2} )\times 2) = \\ = 3 + 2 \sqrt{2} - (16 - 4 \sqrt{2} ) = \\ = 3 + 2 \sqrt{2} - 16 + 4 \sqrt{2} = \\ = - 13 + 6 \sqrt{2} = \\ = \boxed{ 6 \sqrt{2} - 13}[/tex]